Evaluation of large-scale dissemination of Nosema ceranae spores by European bee-eaters Merops apiaster - Valera, F.; Martín-Hernández, R.; Higes, M. (Environmental microbiology reports, 2011)
Summary Identification of transmission routes and of factors affecting the spatial positions of pathogens, hosts and vectors is basic to an adequate disease management. Nosema ceranae is a Microsporidian recently described as a parasite of Apis mellifera honeybees and is currently considered the aetiological agent of an emergent illness named nosemosis type C. In this article we evaluate the role of a bird species, the European bee‐eater, Merops apiaster, as a large‐scale dispersive agent of N. ceranae. We found a high prevalence of viable spores of N. ceranae in pellets regurgitated by bee‐eaters in different locations in the Iberian Peninsula, Central Europe and central Asia. In contrast, spores of Nosema apis, considered till recently the most common microsporidium infecting honeybees, were detected in a single locality and Nosema bombi spores were not noticed. Since non‐viable spores were also found in bee‐eater nests from different locations, this bird species could also reduce the fraction of infected insects by withdrawing pathogens from the colonies. We conclude that bee‐eater mobility and migration may have played an important role in the transmission of the pathogen N. ceranae.